Sofosbuvir/velpatasvir with or without low-dose ribavirin for patients with chronic hepatitis C virus infection and severe renal impairment - Liu, Chen-Hua; Chen, Chi-Yi; Su, Wei-Wen; Tseng, Kuo-Chih; Lo, Ching-Chu; Liu, Chun-Jen; Chen, Jyh-Jou; Peng, Cheng-Yuan; Shih, Yu-Lueng; Yang, Sheng-Shun; Huang, Chia-Sheng; Huang, Ke-Jhang; et al. (Gut, 2022)
ObjectiveData regarding the real-world effectiveness and safety of sofosbuvir/velpatasvir (SOF/VEL) with or without low-dose ribavirin (RBV) in patients with chronic hepatitis C virus (HCV) infection and severe renal impairment (RI) are limited. We evaluated the performance of SOF/VEL with or without low-dose RBV in HCV-infected patients with chronic kidney disease stage 4 or 5.Design191 patients with compensated (n=181) and decompensated (n=10) liver diseases receiving SOF/VEL (400/100 mg/day) alone and SOF/VEL with low-dose RBV (200 mg/day) for 12 weeks were retrospectively recruited at 15 academic centres in Taiwan. The effectiveness was determined by sustained virological response at off-treatment week 12 (SVR12) in evaluable (EP) and per-protocol populations (PP). The safety profiles were assessed.ResultsThe SVR12 rates by EP and PP analyses were 94.8% (95% CI 90.6% to 97.1%) and 100% (95% CI 97.9% to 100%). In patients with compensated liver disease, the SVR12 rates were 95.0% and 100% by EP and PP analyses. In patients with decompensated liver disease, the SVR12 rates were 90.0% and 100% by EP and PP analyses. Ten patients who failed to achieve SVR12 were attributed to non-virological failures. Among the 20 serious adverse events (AEs), none were judged related to SOF/VEL or RBV. The AEs occurring in ≥10% included fatigue (14.7%), headache (14.1%), nausea (12.6%), insomnia (12.0%) and pruritus (10.5%). None had ≥grade 3 total bilirubin or alanine aminotransferase elevations.ConclusionSOF/VEL with or without low-dose RBV is effective and well-tolerated in HCV-infected patients with severe RI.